Ektstrak Kulit Jeruk Nipis dengan Minyak Serai Wangi Stick Balm sebagai Aromaterapi dan Repellent Nyamuk Aedes aegypti - Wulandari, Septi; Riandiani , Evelyne; Romdani , Ayu Nadiyah Permatasari; Elena , Felicitas; Salsabila , Frisya Nutia; Amanda , Savira Intan (Journal of Pharmaceutical and Sciences, 2025)
Lime (Citrus aurantifolia) is a plant that has been empirically recognized to possess insecticidal and repellent properties. Citronella oil (Cymbopogon nardus) is an essential oil with antidepressant properties and is commonly used as aromatherapy. The purpose of this study was to determine the physical properties and mosquito-repellent activity of a stick balm preparation formulated from lime peel extract (Citrus aurantifolia) as a repellent, with the addition of citronella oil (Cymbopogon nardus) as aromatherapy. This study employed an experimental research method. Stick balm preparations were made in four formulations with extract concentrations of 0%, 5%, 10%, and 15%. The formulations were evaluated for organoleptic characteristics, pH, homogeneity, spreadability, smearability, hedonic acceptance, irritation, and the presence of steroids and terpenoids, as well as tested for mosquito-repellent activity against Aedes aegypti. The evaluation results showed that all formulations met the established physical quality standards, indicating good stability and safety. The mosquito-repellent effectiveness test demonstrated that formulation F3 (15% lime peel extract) provided the highest protection at 94.74%, followed by F2 (84.21%), F1 (74.68%), and F0 (42.11%). Thus, stick balm preparations containing lime peel extract and citronella oil are physically stable, safe, and effective as mosquito-repellent aromatherapy, with F3 being the most effective formulation.